Rationalization of Empiric Antibiotics Therapy in Patients Hospital Acquired Pneumonia at the East OKU Regional General Hospital - Niza, Hairun; Hanifah, Sarah; syavira, salsabila regy (Universitas Pakuan, 2023)
The use of antibiotics requires special attention to improve the quality of therapeutic results and prevent antimicrobial resistance. Through judicious administration of antibiotics, it is hoped that there will be an impact on the quality of treatment and control of microbial resistance. The method used in this research is descriptive analysis with a cross-sectional and retrospective research design, collecting data from medical record at East OKU Hospital for the period of 2016-2022. The analysis of the rationalization of the use of empiric antibiotics therapy showed that 65 % fell into the rational category, 35 % were irrational and had a total defined daily dose (DDD) value of 70.96 DDD/100 days of hospitalization.